Congenital Midline Nasal Sinus/cyst - Prof. Masood H. Khan; Dr. F.A. Bhat; Dr. A.H. Khan; Dr. M. Yaseen (Indian Journal of Plastic Surgery)
An unusual presentation of midline nasal sinus associated with dermoid cyst is presented. Two theories of causation are reviewed.